2019
DOI: 10.3390/molecules24071373
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Degradation of Cyanides and Thiocyanates from an Industrial Wastewater

Abstract: We have explored the simultaneous degradation of cyanides and thiocyanate present in wastewaters from a cokemaking factory using photoassisted methods under varied illumination conditions (from simulated solar light to UV light). Overall, the photochemical degradation of cyanides was more efficient than that of thiocyanates, regardless of the illumination conditions, the effect being more pronounced in the absence of a photocatalyst. This is due to their different degradation mechanism that in the case of thio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 32 publications
(50 reference statements)
0
11
2
2
Order By: Relevance
“…However, little support for this type of treatment option was found (Figure 3a) as a rapid destruction method for treating cyanide-containing effluents. This is in contrast to other work that reportedly used simulated natural UV intensities and found rapid degradation of free cyanide and thiocyanates [40]. This result may be due to the UV wavelengths used in our study (285 nm), which fall in the UVB spectrum, whereas Mediavilla et al [40] used a UVC lamp, which emits at shorter wavelengths (254 nm).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…However, little support for this type of treatment option was found (Figure 3a) as a rapid destruction method for treating cyanide-containing effluents. This is in contrast to other work that reportedly used simulated natural UV intensities and found rapid degradation of free cyanide and thiocyanates [40]. This result may be due to the UV wavelengths used in our study (285 nm), which fall in the UVB spectrum, whereas Mediavilla et al [40] used a UVC lamp, which emits at shorter wavelengths (254 nm).…”
Section: Discussioncontrasting
confidence: 95%
“…This is in contrast to other work that reportedly used simulated natural UV intensities and found rapid degradation of free cyanide and thiocyanates [40]. This result may be due to the UV wavelengths used in our study (285 nm), which fall in the UVB spectrum, whereas Mediavilla et al [40] used a UVC lamp, which emits at shorter wavelengths (254 nm). However, Mediavilla et al [40] also reported an irradiance of 26 mW/cm 2 , which is two orders of magnitude higher to that natural UV irradiation (0.2 mW/cm 2 ).…”
Section: Discussioncontrasting
confidence: 95%
“…Por otro lado, la presencia de sulfatos confirma la oxidación de la molécula de tiocianato por acción del permanganato como oxidante (a pesar de los bajos porcentajes de eliminación obtenidos). Un mecanismo similar ha sido propuesto para la oxidación de tiocianato a partir de otros oxidantes (ozono, peróxido de hidrógeno, fotoquímica) (Chung y Wood 1970, Collado et al 2009, 2010, Douglas et al 2012, Viña et al 2019. Asimismo, es interesante destacar que en el caso de la oxidación de tiocianato, al contrario de lo que se observó para el cianuro, es posible detectar cianato antes de su hidrólisis.…”
Section: Aguas Sintéticasunclassified
“…En el caso de la concentración de 200 mg/L, este balance molar es cercano a 1, lo que indica que todo el azufre de las moléculas de tiocianatos degradadas se oxidó a sulfato. Para concentraciones menores de tiocianato se obtuvieron balances molares de 0.5 a 0.9, lo que sugiere la presencia de especies de azufre no detectadas en este estudio tales como sulfuros o polisulfuros (Collado et al 2009, Viña et al 2019. El balance de intermedios nitrogenados (relación molar N-intermedios/SCN en el cuadro II) es ligeramente inferior a la unidad en todos los casos, sugiriendo la presencia de otras especies nitrogenadas además de las formas oxidadas nitrato, nitrito, amonio.…”
Section: Aguas Sintéticasunclassified
“…Although SCN − is almost seven times less toxic than CN − (Woffenden et al 2008;Kuyucak and Akcil 2013), the greater chemical stability of SCN − compared to its parent compound (Akcil 2003) leads to its accumulation in mining waste streams (Woffenden et al 2008), as well as its environmental persistence (Mediavilla et al 2019). Therefore, although not explicitly addressed in regulatory guidelines for discharge of CN − -bearing mine effluents, SCN − is still considered by regulatory agencies to be a threat to aquatic wildlife (Bhunia et al 2000;Gould et al 2012).…”
Section: Introductionmentioning
confidence: 99%